Pre-operative DTI and probabilisitic tractography in four patients with deep brain stimulation for chronic pain. - Owen, S; Heath, J; Kringelbach, M; Green, A; Pereira, E; Jenkinson, E; Jegan, T; Stein, J; Aziz, T (2008)
This study aimed to examine, using diffusion tensor imaging (DTI), differences in electrode placement in four patients undergoing deep brain stimulation for chronic neuropathic pain of varying aetiology. A pre-operative DTI was obtained for each patient, who was then implanted with deep brain stimulation electrodes in the periventricular/periaqueductal grey area with good pain relief. Using seeds from the postoperative MRI scan, probabilistic tractography was performed from the pre-operative DTI.